Tectonosedimentary episodes of the South Limón Basin - Bottazzi-Basti, Giovanni (2021)
The study area is located on the South Limón back-arc basin, on the southeastern part of Costa Rica. The objective of this research is the study of sedimentologic-stratigraphic sequences, referenced to the tectonic framework of Costa Rica. The methodology involved literature review and field work to develop a sedimentologic framework, sequence stratigraphy and tectonic analysis with reference to main regional events of Costa Rica. The conformation of South Limón Basin, since Upper Cretaceous, presents a predominant progradational stratigraphy. Its filling, during Cenozoic time, is documented sedimentologic and sequentially, and correlates with main regional and local tectonic events, in concomitance with eustatic changes, which evidence particular characteristics, inducing a geographic and environmental evolution, differentiated from other basins. Its paleogeographic evolution is consistent with sedimentary systems that show this progradation; starting on abyssal basin environments up to its fullness, during Upper Tertiary and Early Quaternary, by alluvial and shallow marine sedimentary systems. Particularly, the last compressive tectonic stage, documented on the sedimentologic record, since Miocene, is directly related to seismic mechanisms, analogous to the event of April 1991 that resulted in the Limón earthquake.